Analysis of Indonesian Students’ Error in Solving Mathematical Literacy Problems Based on PISA 2015 Results - Setiawati, Santy; Herman, Tatang; Jupri, Al (FKIP Universitas Lampung, 2020)
This study aims to describe the students’ error in solving mathematical literacy problems with focused on level 3 and 4 based on PISA 2015. Qualitative research was used in this study with a descriptive approach. The subjects of this study were 61 students at seventh grade consisted of 28 students from SMPN 14 Bandung and 33 students from SMPN 9 Bandung. The instrument consisted of four questions designed and interview guidelines. Data were analyzed descriptively based on written test results and interviews to confirm students’ work. The results of this study showed that 65.3% of students made mistakes in solving mathematical literacy level 3 and 73.68% of students made mistakes in solving mathematical literacy level 4. Students’ error that arise in solving these mathematical literacy problems are understanding the problem and choosing the information to get a solution. Based on the results, researcher suggest that the preparation of sentences in the mathematical literacy problem, it should be emphasized with the precise sentences, so that the purpose of the problem is well understood by students. Keywords: students’ error, mathematical literacy problems level 3 and 4, PISA 2015 results, junior high school students. DOI: http://dx.doi.org/10.23960/jpmipa/v21i1.pp67-77